2018
DOI: 10.1101/309989
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cycles of gene expression and genome response during mammalian tissue regeneration

Abstract: Background: Compensatory liver hyperplasia -or regeneration -induced by two-thirds partial hepatectomy (PH) permits the study of synchronized activation of mammalian gene expression, particularly in relation to cell proliferation. Here, we measured genomic transcriptional responses and mRNA accumulation changes after PH and sham surgeries. Results:During the first 10-20 hours, the PH-and sham-surgery responses were very similar, including parallel early activation of cell-division-cycle genes. After 20 hours, … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…We profiled H3K4me3, Pol II (RPB2 subunit), and Pol III (RPC4 subunit) occupancy in parallel at different time points after PH by chromatin immunoprecipitation followed by high throughput sequencing (ChIP-seq). The Pol II and H3K4me3 occupancy data have been used to study occupancy dynamics at Pol II genes (11). Here, we used the same data as well as the Pol III data to determine occupancy scores at Pol III genes, as described before (18) (Supplementary Table S1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We profiled H3K4me3, Pol II (RPB2 subunit), and Pol III (RPC4 subunit) occupancy in parallel at different time points after PH by chromatin immunoprecipitation followed by high throughput sequencing (ChIP-seq). The Pol II and H3K4me3 occupancy data have been used to study occupancy dynamics at Pol II genes (11). Here, we used the same data as well as the Pol III data to determine occupancy scores at Pol III genes, as described before (18) (Supplementary Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…Expressed Pol III loci differ from silent ones by the nearby presence of histone marks such as H3K4me3 (2,6–8,10) typical of chromatin regions that are or have been actively transcribed by Pol II ((11) and references therein). Moreover, active Pol III loci tend to reside close to Pol II TSSs and to peaks of Pol II occupancy, which suggests that transcription of nearby Pol II and Pol III genes is somehow co-regulated (2,5–8,10).…”
Section: Introductionmentioning
confidence: 99%
“…We next investigated the expression pattern of TLR5 in the liver of mice after PHx. Global transcriptome analysis of the mouse liver at various time points following PHx revealed a signi cant upregulation of TLR5 along with other TLRs (GSE95135) [29] (Fig. 1b).…”
Section: Tlr5 Is Up-regulated In the Liver After Phxmentioning
confidence: 99%
“…The contemporaneous presence of genes for adaptive immunity, complex nervous circuits, or for other amniote functions somehow determines regeneration failure, as schematically indicated in Figure 5b,c. The analysis of the transcriptomes of healing skin and other mammalian organs (Brant et al, 2019;Li et al, 2001;Khaspur et al, 2013;Sass et al, 2017;Rib et al, 2018; Table 3) shows that inflammatory and immune genes have increased as number and types, starting from reptiles (Boehm, 2012;Zimmerman et al, 2008). It has been suggested that, like in anurans (Harty et al, 2003;Mescher et al, 2016;Tsujioka et al, 2015), the high immune competence reached in amniotes eliminates every "embryonic-like" type of antigen, including those formed after wounding so that a regenerative blastema cannot form (Alibardi, 2015(Alibardi, , 2017b(Alibardi, , 2019d.…”
Section: Genes Activated During Wound Healing In Amniotesmentioning
confidence: 99%